The assessment on the acceptance of waste materials as a partial cement replacement in Malaysia construction industry - Zaidatul Syahida, Adnan (2022)
In Malaysia, the construction works have been increasing in several years. However, the increased number of construction works have led to an increase of cement production. The production of cement itself has caused wider environmental implications which is the main cause of global threat issues. To control the problem, several researches has been conducted in the past few decades to find new waste materials that have the same chemical and mechanical properties which can be used as a partial cement replacement in construction. Most of the results showed a positive performance of concrete containing waste materials, unfortunately this research stopped at the research stage only where all of these waste materials are rarely used in the construction industry. This is because, most industry in Malaysia do not use these waste materials as a partial cement replacement in their construction work due to unclear reasons. Therefore, this study has been conducted to investigate the factors of un-utilizing of waste materials as a partial cement replacement in Malaysia’s construction industry from an industrial perspective. This study aims to investigate the acceptance of waste materials as a partial cement replacement. To achieve that aim, the objectives are to (1) To analyse the properties and performance of waste materials in concrete; (2) To identify the factors of un-utilizing waste materials as a material for partial cement replacement (3) To identify a suitable solution to utilize the use of waste materials in the Malaysian construction industry. The first objective can be achieved by intensive literature review on the properties and performance of waste materials in concrete and an interview session with 10 experts from the government and private sector which are Jabatan Kerja Raya (JKR), registered contractor Class G1-G7, consultants as well as suppliers. To achieve second and third objective, a total of 140 sets of questionnaire surveys were distributed to all the respondents from a construction site background in Malaysia. The data obtained from the interview sessions and questionnaire design on the factors of un-utilizing of waste materials as a partial cement replacement and the solutions to overcome the related problems has been analysed by using the Relative Importance Index method (RII). Before conducting the RII, Common Method Bias (CMB) and Cronbach’s Alpha analysis, ɑ has been conducted to investigate the reliability of the study and the results for CMB is 32.665 % and ɑ=0.976. From the RII analysis, the main factors of un-utilizing of waste materials are (1) The company, client and end user are unfamiliar with the type of waste materials available; (2) The company, client and end user fear a product failure and service life of construction using waste materials, (3) Lack of quantitative data on the properties of concrete using waste materials; (4) Company, client and end user fear that the quality of concrete containing waste materials are not the same with the quality of normal concrete; (5) Lack of general knowledge regarding the usage and benefits of waste materials; (6) The company is not sure of the buyer’s acceptance; (7) Lack of market to buy waste materials; (8) Lack of equipment to process the waste materials before used in cement; (9) The company does not have special permits and regulations to use waste materials; (10) Extra space needed to store waste materials before been used; (11) Financial and time constraints in processing waste materials. Therefore, the suitable solutions are; (1) Industry should be more open and innovative; (2) Universities and industry should create a better connection; (3) More research, analysis and data regarding waste materials should be done; (4) More educational programmes and conferences should be conducted; (5) Government should play a role by approving and including the usage of waste materials in a clause. Thus, this study can be a reference to overcome the study problem.